Strategi Bertahan Hidup Tukang Becak di Kota Makassar - Andi Yusrita (Jurnal Commercium: Kajian Masyarakat Kontemporer, 2019)
The study aims at examining the dynamics of socio-economic of pedicab drivers and the survival strategy of pedicabdrivers.The data obtained in this study were analyzed using qualitative description analysis through three stages, namely data reduction, data presentation and conclusion drawing. Data collection techniques used were observation, interviews, and documentation.The results of the study reveal that the family needs have not sufficiently fulfilled because the husband’s income as the pedicab drivers has yet to fulfill the daily needs. The needs in this case is food, clothing, shelter as well as education and healthcare. To solve that, there are several strategies conducted by them in fulfilling their needs, namely using active strategy which covered doing side-job, involving family members to obtain income; passive strategy by saving several posts such as getting cheaper food, buying food when the price is lower, and saving small income for major needs; and network strategy by borrowing some money from neighbor or family. Then, they also get aids from government in a form of health insurance shown in KIS card given for free.